(3TQM QSGdI GdJhMjO ddHQchjs - (3GdMSjfj, GdNGOej, GdfbTHfOj, GdMfaj, CHh SYjO, eMeO Hf eUWai Hf YKeGf, J (B1176 (3g`s ((3YKeGf Hf eMeO Hf YHO GdQRGbs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg MeO GdehMOjf hHYO aGdcdeGJ GdBJjI GdefShHI Edi GdEeGe GdHQchj deG cGfJ XGgQI YHGQI UhajI eMJedI dchfgG cdGejI ChQOfG aj HjGf eWdHjfs
(3BNQgG (B:s
(3gPG gh GdcdGe Ydi GdcdGe HMSH hSY GdMGd hGdebGe Ydi eG jbJVjg YHGQGJge Efg Ydi XGgQgG aYdi XGgQg hEf Ydi JChjd aYdi JChjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 68s
(3eYLe GdeDdajf (B3 / 692s
(3SQcjS (B808s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds